Chemical and physical properties of the flour prepared from unpared dehydrated coconut (Cocos nucifera Linn.) - Abdon, Isabel (Concepcion) 1917-; Smith, Donald B. (1967)
Coconut flour was prepared by pre-pressing and solvent extraction of unpared edible dehydrated kernels processed by chemical dip treatment. The chemical and physical properties as well as the nutrient and amino acid composition of the flour was studied. The protein conetent is 24.9%, the fat is 2% and the crude fiber is 9.8%. The pH valu is 4.5. The flour is particularly rich in methionine and valine, but low in other essential amino acids. Tryptophan was found to be the limiting amino acid. Negative results were obrained for rancicidity tests done after 3 months storage at room and refrigerated temperatures. TYhe results of this study show that the flour is a potential raw material for the preparation of high protein food products from vegetable sources.
Thesis (M.S. Food Technology)--University of the Philippines, Diliman.
Keywords: Flour; Coconut